The reflection of shahdazi and military characteristics of Khorasani’s style in Kurdish classical poetry - Mohammed, Abdi H.; Khalil, Kamaran I.; Adak, Abd Al Rahman (Humanities Journal of University of Zakho, 2019)
Although the emergence of Persian Classical Poetry is related with the imitation of the Arabic ancient Poetry, and the features of Persian (qasida) are mostly closed to the Arabic Poetry, hence, this poem has a set of characteristics which are generally the environmental production of Iranian Poetry. One of the characteristics is overcoming the Same-sex character homosexuality and military character of the palace of wealthy,(Samani) , (Ghaznavi), and (Seljukian) Authoritative on the (Taghazul) of beginning of (Qasidas). During the reigns of these countries, due to the attacks and invasions that were held by them, the existence of servants and their usage for different purposes , and glorifying the military forces and fighters particularly Turkish ones were occupied the major part of imageries and (Ghazali) expressions in Persian Poets’ works. Apparently, by passing periods of time and especially after the weakness of (Qasida) form, Persian poets continued to imitate these characteristics to an extend that the Persian poets were mostly describing a character is referring to a male attractive fighter. So, these phenomena might be the results of transforming the imitation of Persian poetry into Kurdish poetry, additionally, Kurdish classical poets depicted the male fighter –lover variously or the images that were used by them were the production of the impact of homosexuality -military impression of qasida in Khorasani’s style.